ANALISIS PERSEPSI NASABAH ATAS KEAMANAN DAN KEPERCAYAAN DALAM SISTEM e-PAYMENTS - Petrus Hari Kuncoro Seno (Politeknik Negeri Jakarta, 2012)
This research made a study on the security and trust in the relation to the Electronc Payments System (EPS) . The research propose a model which discuses factors which determine the perceived security and the perceived trust. This research also discus the effects of perceived security dan trust in the use of EPS, In this research there has been an emprirical test of the proposed model with respondens of 316 people in the Jakarta Meropolitan area. Data was analized using a structural equation modelling. The research finding shows that security statements is a factor which is significant to increase the perceived security in the usage of EPS. The perceived trust has a positif influence significanly in the use of EPS. The research did not find any statistical proving that there is a statistical relationship between the quality of transaction procedure with the preceived security and perceived trsutin the use of EPS. This research also proves that there is a statistical relationship between the technical protection and the perceived security (H1) , the security statements with the perceived trust (H6). This research did not find any statistical relationship between the transaction procedure the perceive trust (H4) and the technical protection with the perceived trust (H2), This research explained the relationship between the perceived trust and the use of EPS. The finding of the research shows the role of the perceived security in the building of the user security and the positif influence of the the perceived trust to the use of EPS. The effects of the security statements for the user perception of security and trust also has been validated. The perceived security is an essential consept in the attempt ti understand the use of EPS. Keywords:E-payments, Security, Trust, Consumers’ Perception, use of EPS